ДО ПРОБЛЕМ РОЗВИТКУ ІНФОРМАЦІЙНОЇ КУЛЬТУРИ (Педагогіка вищої та середньої школи, 2002)
The modem person feels on himself the greatest streams of the information. The information is one of the main values of mankind, the most important resource of his life-support. Now it is necessary to bring up the person who simply owns a constant increase of the information stream, person with high intellectual potential.Successfully to acquire extremely high quantity of the information, competently to solve a circle of problems which puts the modernity, first of all, the person should reach a high level of information culture.Statement of information culture of the person begins from the early age and proceeds during the all life. The modern person needs computer grammatical correctness, skill to use information technologies, to have fa st orientation in a stream of the oral and written information, to have necessary cultural and intelligent luggage, skillfully to use it in any field of activity.The concept "The Information culture" is given birth by computer - technological progress in an atmosphere of which three is a development of a modern civilization and made step-by-step transition to an information society.